The End of the Book : A Novel - Shreve, Porter (Book collections on Project MUSE., 2014)
The End of the Book is the story of an aspiring contemporary novelist who may or may not be writing a sequel to Sherwood Anderson's classic Winesburg, Ohio. Adam Clary works in Chicago for a famous internet company on a massive project to digitize the world's books, but secretly he hates his job and wishes to be a writer at a time when the book as physical object and book culture itself have never been more threatened. Counterpointing Adam's story is that of George Willard, the young protagonist of Anderson's book, who arrives in Chicago around 1900 when it was the fastest-growing city in America.